Dependency injection in .NET - Seemann, Mark (Manning, 2012)
Dependency Injection in .NET presents core DI patterns in plain C# so you'll fully understand how DI works, covers integration with standard Microsoft technologies like ASP.NET MVC, and teaches you to use DI frameworks like Structure Map, Castle Windsor, and Unity. About the Technology Dependency Injection is a great way to reduce tight coupling between software components. Instead of hard-coding dependencies, such as specifying a database driver, you inject a list of services that a component may need. The services are then connected by a third party. This technique enables you to better manage future changes and other complexity in your software. About this Book Dependency Injection in .NET introduces DI and provides a practical guide for applying it in .NET applications. The book presents the core patterns in plain C#, so you'll fully understand how DI works. Then you'll learn to integrate DI with standard Microsoft technologies like ASP.NET MVC, and to use DI frameworks like StructureMap, Castle Windsor, and Unity. By the end of the book, you'll be comfortable applying this powerful technique in your everyday .NET development. This book is written for C# developers. No previous experience with DI or DI frameworks is required. What's Inside Many C#-based examples A catalog of DI patterns and anti-patterns Using both Microsoft and open source DI frameworks Tabel of Contents PART 1 PUTTING DEPENDENCY INJECTION ON THE MAP A Dependency Injection tasting menu A comprehensive example DI Containers PART 2 DI CATALOG DI patterns DI anti-patterns DI refactorings PART 3 DIY DI Object Composition Object Lifetime Interception PART 4 DI CONTAINERS Castle Windsor StructureMap Spring.NET Autofac Unity MEF.